L19 Optimisation of potent, selective and brain penetrant atm inhibitors as potential therapeutic agents for HD. (13th September 2016) - Toledo-Sherman, Leticia; Chachope, Roger; Rose, Mark; Munoz-Sanjuan, Ignacio; Breccia, L Perla; Bate, Jennipher; Matthews, Kimberly L; Wilshart, Grant; Vater, Hugh; Jarvis, Rebecca; Lazari, Vad; Barnes, Kate; et al.
Abstract : Emerging evidence shows that the ATM signalling pathway is dysregulated in neurodegenerative disorders including Huntington's disease (HD). ATM signalling has been shown to be elevated in cells derived from HD patients and mouse models of HD. Genetic and pharmacological evidence from cellular and animal models of HD suggests that reduction of ATM signalling can ameliorate mHTT toxicity. Thus inhibitor of ATM kinase presents a promising therapeutic intervention strategy for the treatment of HD. We present data from our medicinal chemistry program which aims to develop potent, selective and brain-penetrant ATM inhibitors. Chemical optimisation of CNS-compliant physical chemical properties led to the identification of compounds suitable for a proof-of-concept study in HD models. Our lead compound, CHDI-00485194, displayed excellent oral bioavailability and pharmacokinetics. PO administration to mice showed distribution into brain (brain:plasma ratio of 1.3) and linear pharmacokinetics in a dose escalation study. An acute PK/PD biomarker study to evaluate the effect of CHDI-00485194 on irradiation induced DNA damage biomarkers showed a significant dose-dependent inhibition of KAP1 phosphorylation by CHDI-00485194 at 30 and 60 minutes post-irradiation.